Optimization os the Sinar Applications (Precision National Driver’s Licence) in the Process of Issuing Driver’s Licenses in the Jurisdiction of Bengkulu City Police - Megawati Megawati; Halimah Halimah; Sutrisno Sutrisno; Yudhi Hery Setiawan (Universitas Muhammadiyah Mataram, 2026)
This study discusses the optimization of the use of the SINAR application (Precision National Driver's License) as a digital-based public service innovation implemented by the National Police of the Republic of Indonesia in the process of making a Driver's License (SIM). This application aims to improve the quality of service through a system that is fast, transparent, efficient, and easily accessible online. The public can register for a new driver's license or renewal online without having to come directly to the service office in the early stages of administration. The focus of the research is the optimization of the implementation of SINAR in the jurisdiction of the Bengkulu Police as well as its supporting and inhibiting factors. The research uses a qualitative approach with data collection techniques through interviews, observation, documentation, and triangulation. The results of the study show that the implementation of SINAR provides ease of access to services, speeds up the administrative process, reduces queues, and increases service transparency. However, there are still obstacles such as low public understanding of digital applications, internet network disruptions, and the tendency of some people to use manual methods. In conclusion, the optimization of SINAR is able to increase the effectiveness of public services in the field of traffic and support the transformation of the National Police towards a modern technology-based institution. Optimization efforts are carried out through increasing socialization, improving technological infrastructure, and increasing the capacity of human resources.